Women’s Voluntaristic Actions in Playing Multiple Roles (A Study on Home worker Housewives from Underprivileged Families in Polehan Village, Malang) - Ani Widiah Qusminingrum; Wahyudi Wahyudi; Sulismadi Sulismadi (Jurnal Perempuan dan Anak, 2021)
Women are creatures who have been assumed as the second-class citizens or only engaged in domestic activities. It arises because of the feminine nature that has been attached to women. However, as time goes by, the rules and values ​​of women have changed. The emancipation movements appear to bring women to work in the economic sector to take multiple roles. The purpose of this research is to find out how the actions of housewives in running dual roles. This research uses qualitative approach with descriptive method. Qualitative descriptive is a method in examining the status of a group of people, an object, a set of conditions, a system of thought or a class. The subject of this study as many as ten people. Informant determination technique in this research conducted by purposive sampling technique, the informants are selected based on the characteristics or the predetermined character. Data analysis techniques used are data collection, data reduction, data presentation, conclusion and data verification. The theory used to analyze this research is Talcott Parsons' voluntaristic action theory, in which a person performs a certain purpose of action. In addition, the aim is achieved by referring to the values ​​and norms, using the tools and means as capital goals by looking at the conditions and circumstances around it. The results showed that the purpose of housewives performing dual role acts is to improve the family economy as well as the form of self-actualization as a wife, mother a nd a worker. Then, in order to achieve these goals, housewives perform a dual role as home workers, while upholding the values ​​and norms, using the tools and facilities owned, and still pay attention to the conditions and situation surrounding her.